2017
DOI: 10.1186/s12969-017-0196-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth and weight gain in children with juvenile idiopathic arthritis: results from the ReACCh-Out cohort

Abstract: Background: With modern treatments, the effect of juvenile idiopathic arthritis (JIA) on growth may be less than previously reported. Our objective was to describe height, weight and body mass index (BMI) development in a contemporary JIA inception cohort. Methods: Canadian children newly-diagnosed with JIA 2005-2010 had weight and height measurements every 6 months for 2 years, then yearly up to 5 years. These measurements were used to calculate mean age-and sex-standardized Z-scores, and estimate prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
0
29
1
1
Order By: Relevance
“…The percentage of patients with inactive disease after 1 year of therapy in our study was >2‐fold higher than the percentages in other prospective trials using biologic agents as second‐ or third‐line therapy in systemic JIA . Furthermore, the incidence of articular damage, growth failure, obesity, and functional limitations was ~3 times lower than in recent observational cohorts .…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The percentage of patients with inactive disease after 1 year of therapy in our study was >2‐fold higher than the percentages in other prospective trials using biologic agents as second‐ or third‐line therapy in systemic JIA . Furthermore, the incidence of articular damage, growth failure, obesity, and functional limitations was ~3 times lower than in recent observational cohorts .…”
Section: Discussioncontrasting
confidence: 74%
“…Unfortunately, the first trials demonstrated completely inactive disease in only 30% of patients after the first year of therapy, and biologic therapy was often combined with other glucocorticoids and/or other DMARDs. In recent inception cohorts, ~50% of the patients with new‐onset disease had inactive disease after 1 year and 70% after 3 years of therapy . In addition, 50–60% of patients with systemic JIA received long‐term systemic glucocorticoids, which are associated with severe and longstanding side effects such as growth failure and obesity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…growth velocity. 33 The most optimal way to prevent complications is to use steroids as short as possible, in the lowest acceptable doses.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive treatment with calcium and vitamin D should not be underestimated in the prevention of disease complications. 33 The frequency of growth retardation in sJIA has been reported as 10%-20% in different studies. 34 In a national sJIA cohort from Germany, the percentage of growth retardation was 23%.…”
Section: Discussionmentioning
confidence: 99%